2012
DOI: 10.1583/12-3881.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of the 8-F Angio-Seal Vascular Closure Device in Large-Caliber Arteriotomies

Abstract: The use of the 8-F Angio-Seal VCD to close large-caliber arteriotomies ranging from 9-F to 12-F is feasible and safe, with a low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
2
11
1
Order By: Relevance
“…In contrast, in the present study, any size of puncture site hematoma or bleeding from the access site was considered a type 1 complication, and type 1 complications accounted for 4 80% of all complications. From all the previous reports on the 8-F Angio-Seal and its use for 4 8-F femoral access, Sarin et al (13) had the most similar conditions to those of the present study. In line with our study, Sarin et al reported their experiences using the 8-F Angio-Seal for the closure of 9-F to 12-F femoral access.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast, in the present study, any size of puncture site hematoma or bleeding from the access site was considered a type 1 complication, and type 1 complications accounted for 4 80% of all complications. From all the previous reports on the 8-F Angio-Seal and its use for 4 8-F femoral access, Sarin et al (13) had the most similar conditions to those of the present study. In line with our study, Sarin et al reported their experiences using the 8-F Angio-Seal for the closure of 9-F to 12-F femoral access.…”
Section: Discussionsupporting
confidence: 81%
“…Sarin et al (13) reported no immediate complication, whereas the present study reported a type 1 complication in 9 of 11 complications, including hematoma and oozing occurring immediately after the deployment of the 8-F Angio-Seal device. Also, Sarin et al applied manual compression for 15 minutes after Angio-Seal deployment in all patients as per their protocol, and 5 of 42 patients were not given anticoagulation.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Additionally, in our experience of vessel closure outside of EVAR, the Angio-Seal device has been used to successfully close access sites slightly larger than the recommended sheath sizes, with an 8-French AngioSeal closing up to 12-French sheath sites. This use of Angio-Seal is outside of its licenced indication but has been reported to be feasible and safe [16].…”
Section: Discussionmentioning
confidence: 99%
“…With disease-free access sites, we will use the 8-F device in up to 12-F access sites as has been described. 13 This is our device of choice for after thrombolysis and soon to be anticoagulated patients given the sandwich effect of the arteriotomy. We have used this device in proximal superficial femoral artery (SFA) (retrograde and antegrade) as well as distal external iliac artery access sites, both with success.…”
Section: Operators' Experiencementioning
confidence: 99%